Wireless power transmission applied to pure electric vehicle - Jorgetto, Marcus F. C.; E Melo, Guilherme De A. [UNESP]; Alves, Marcos G. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper proposes a methodology of design and control, and shows the main simulation and experimental results for a LLCC Series-parallel resonant converter applied to Wireless Power Transmission (WPT) in-motion. Using Induced Power Transfer (IPT) and considering a near-field energy-Transfer method (less than 20 cm), the converter is applied in a small scale electric vehicle (EV). The modeling was derived from inductors with cylindrical spiral shape, considering series association for the emitter. The resonant converter achieves high efficiency (up to 86%) along the full length of the experimental emitter arrangement. Furthermore, an important contribution presented in this paper is the analysis and design of arrangements for the inductive elements of WPT, and the small signal theory applied to a Full-Bridge Phase-Shift (FB-PS) resonant converter. Experimental results are shown for a prototype rated at 1150W, in order to validate the proposed methodology and system, considering wireless energy transfer with 30 mm gap.
Keywords: Electric Vehicles; Fast charging; Inductive Power Transfer; Light transport vehicles; Wireless Power Transmission